Simiao San alleviates hyperuricemia and kidney inflammation by inhibiting NLRP3 inflammasome and JAK2/STAT3 signaling in hyperuricemia mice. (10th August 2023) - Zhang, Yueyi; Wang, Shan; Dai, Xuan; Liu, Tianyuan; Liu, Yage; Shi, Hanfen; Yin, Jiyuan; Xu, Tianshu; Zhang, Yanfei; Zhao, Dandan; Sukhorukov, Vasily; Orekhov, Alexander N.; et al.
Abstract : Ethnopharmacological relevance: Simiao San (SmS), a famous traditional Chinese formula, is clinically used to treat patients with hyperuricemia (HUA). However, its mechanism of action on lowering uric acid (UA) and inhibiting inflammation still deserves further investigation. Aim of the study: To examine the effect and its possible underlying mechanism of SmS on UA metabolism and kidney injury in HUA mouse. Materials and methods: The HUA mouse model was constructed with the combined administration of both potassium oxalate and hypoxanthine. The effects of SmS on UA, xanthine oxidase (XOD), creatinine (CRE), blood urea nitrogen (BUN), interleukin-10 (IL-10), interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) were determined by ELISA or biochemical assays. Hematoxylin and eosin (H&E) was used to observe pathological alterations in the kidneys of HUA mice. The expression levels of organic anion transporter 1 (OAT1), recombinant urate transporter 1 (URAT1), glucose transporter 9 (GLUT9), nucleotide binding domain and leucine rich repeat pyrin domain containing 3 (NLRP3), Cleaved-Caspase 1, apoptosis-associated speck like protein (ASC), nuclear factor kappa-B (NF-κB), IL-6, janus kinase 2 (JAK2), phosphor (P)-JAK2, signal transducers and activators of transcription 3 (STAT3), P-STAT3, suppressor of cytokine signaling 3 (SOCS3) were examined by Western blot and/or immunohistochemical (IHC) staining. The major ingredients in SmS were identified by a HPLC-MS assay. Results: HUA mouse exhibited an elevation in serum levels of UA, BUN, CRE, XOD, and the ratio of urinary albumin to creatinine (UACR), and a decline in urine levels of UA and CRE. In addition, HUA induces pro-inflammatory microenvironment in mouse, including an increase in serum levels of IL-1β, IL-6, and TNF-α, and renal expressions of URAT1, GULT9, NLRP3, ASC, Cleaved-Caspase1, P-JAK2/JAK2, P-STAT3/STAT3, and SOCS3, and a decrease in serum IL-10 level and renal OAT1 expression as well as a disorganization of kidney pathological microstructure. In contrast, SmS intervention reversed these alterations in HUA mouse. Conclusion: SmS could alleviate hyperuricemia and renal inflammation in HUA mouse. The action mechanisms behind these alterations may be associated with a limitation of the NLRP3 inflammasome and JAK2/STAT3 signaling pathways. Graphical abstract: Image 1 Highlights: Renal inflammation occurs in acute hyperuricemia (HUA) mice. Simiao San (SmS) promotes uric acid metabolism by regulating transporter proteins in HUA mice. SmS improves renal injury through inhibiting NLRP3 inflammasome and JAK2/STST3 signaling in HUA mice.